KARAKTERISASI FISIKOKIMIA TEH HERBAL DARI DAUN JAMBU BIJI (Psidium guajava) DAN JAHE MERAH (Zingiber officinale Var. Rubrum) - Asmeri Lamona (Jurnal Kesehatan Lentera 'Aisyiyah, 2024)
This research aims to determine the effect of adding red ginger and drying time on the physicochemical characteristics of guava leaf herbal tea. The research was conducted using a Factorial Completely Randomized Design consisting of 2 (two) treatments consisting of the drying temperature factor (S) with 3 (three) levels S1: 40oC, S2: 50oC and S3: 60oC and the red ginger powder concentration factor (J ) with 3 (three) levels J1 : 2%, J2 : 4% and J3 : 6%. Data were analyzed using ANOVA followed by the Least Significant Difference test. The results showed that the average water content of tea was 11.05%, yield 37.31% and antioxidant content 39.54%. The drying temperature (S) had a significant effect on the water content, yield and antioxidant content of guava leaf tea and the addition of ginger powder (J) had a significant effect on the antioxidant content and had an insignificant effect on the water content and yield of guava leaf tea as well as the interaction between drying temperature and the addition of ginger powder had a significant effect on the antioxidant test and had no significant effect on the water content of guava leaf tea. The best treatment was at a drying temperature of 50oC and the addition of 4% ginger powder (S2J1) which produced good quality guava leaf tea with chemical properties, namely water content of 10.38%, antioxidant content of 55.52% and yield of 33.93%.